Prevalence of hepatitis c virus antibodies in hemodialysis patients - Gürsel ÖZGÜR; Salih Ö. ÇOLAKOĞLU; Neslihan SEYREK; Yahya SAĞLIKER; Saime PAYDAŞ; Hikmet AKKIZ (Turkish Journal of Gastroenterology, 2019)
-